The Influence of Planning towards Educational Management in Realizing Madrasah Educational Governance - Hidayat, Yusuf; Herniawati, Ani; Jahari, Jaja; Erihadiana, Mohamad (CV. Tripe Konsultan, 2024)
This study aims at discussing the influence of planning towards educational management in realizing madrasah educational governance at Madrasah PUI Ciamis. In the present study, the reseachers employed quantitative methodology under survey technique through reviewing rational relationships among planning, educational management, and madrasah educational governance. The research site of the present study was conducted at Madarasah Aliyah (Islamic High School) PUI Ciamis Regency with the total population of 30 respondents. The results of the study showed that based on statistical calculations, testing the main hypothesis (variable X® variable Y® variable Z) obtained Fcount score of 13.8256 that is higher than Ftable score of 3.3690. Based on these scores, it can be concluded that H0 is rejected, meaning that there is a significant influence on planning towards educational management in realizing madrasah educational governance. The conclusion is to realize madrasah educational governance, it can be reached by optimizing planning and educational management.